2020
DOI: 10.17998/jlc.20.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering and Reversing Immunosuppressive Cells in the Treatment of Hepatocellular Carcinoma

Abstract: Use of immune checkpoint inhibitors (ICIs) in hepatocellular carcinoma (HCC) has been partially successful. However, most HCC patients do not respond to immunotherapy. HCC has been shown to induce several immune suppressor mechanisms in patients. These suppressor mechanisms include involvement of myeloid-derived suppressor cells, regulatory T-cells, functionally impaired dendritic cells (DCs), neutrophils, monocytes, and tumor associated macrophages. The accumulation of immunosuppressive cells may lead to an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 152 publications
0
5
0
Order By: Relevance
“…Exhausted T cells show upregulated expression of several inhibitory receptors, including PD-1, and its ligand PD-L1 is expressed on various cells, including tumor cells and antigen-presenting cells [ 29 ]. Previous studies have reported immunomodulatory activity of lenvatinib in terms of adaptive immunity [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Exhausted T cells show upregulated expression of several inhibitory receptors, including PD-1, and its ligand PD-L1 is expressed on various cells, including tumor cells and antigen-presenting cells [ 29 ]. Previous studies have reported immunomodulatory activity of lenvatinib in terms of adaptive immunity [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…33 Clec4F and Tim4 are expressed in KCs but are not present in infiltrating MoMfs. 33,34 Accounting for approximately 20% of hepatic nonparenchymal cells, KCs have a key role in host defense and coordinate the inflammatory response when they detect pathogens. 35 They are involved in phagocytosis, antigen processing and presentation, and the production of proinflammatory mediators.…”
Section: Origins and Functions Of Liver Macrophagesmentioning
confidence: 99%
“…52 Macrophage polarization is influenced by tumor stage and differs among tumors or areas within a tumor. 34 HCC tumor progression was once considered to be associated with a skew in the macrophage phenotype from M1 to M2 phenotypes. 33,53,54 However, recent single-cell analyses have revealed coexisting M1 and M2 signatures in TAMs, indicating that the TAM phenotype may not be simply defined by using the classical M1/M2 model.…”
Section: Origins and Functions Of Tams In Hccmentioning
confidence: 99%
See 2 more Smart Citations